The Green Shoe Option’s Effectiveness at Stabilizing the IPO’S Stock Price on the Indonesian Stock Exchange (2000-2013) - Siti Saadah; Yunia Panjaitan (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2016)
The increased of price volatility due to positive initial returns will reduce investor confidence and impact on the overall market. Market stabilization mechanism is needed to control the price volatility. This research is intended to explore the effectiveness of Green-Shoe Option in reducing stock price volatility after IPO. This study is done through GARCH model development intended to identify the volatility of IPO shares price. This research compares the volatility price of company shares that apply Green shoe option at IPO with companies that do not apply it. The result of this research on companies that conduct IPO on 2000-2013 periods showed that the green shoe option stabilization program which was used by the issuers was effective in muffing the stock prices’ volatility. Therefore, according to researchers Green Shoe Option stabilization program can be used to prevent or ease the drop of shares price under Public offering.